Metal-Ligand Coordination Induced Ionochromism for π-Conjugated Materials - Liu, Jinhui; Han, Long; Geng, Jieting; Hua, Jing; Wang, Zhaobo (Frontiers in Chemistry, 2020)
Recent studies indicated that the toxicity of heavy metal ions caused a series of environmental, food, and human health problems. Chemical ionochromic sensors are crucial for detecting these toxicity ions. Incorporating organic ligands into π-conjugated polymers made them receptors for metal ions, resulting in an ionochromism phenomenon, which is promising to develop chemosensors for metal ions. This review highlights the recent advances in π-conjugated polymers with ionochromism to metal ions, which may guide rational structural design and evaluation of chemosensors.